Zagreb indices and Zagreb coindices of the line graphs of the subdivision graphs. (17th August 2020) - Saidi, Nur Hafiza Azwani Mohd; Husin, Mohamad Nazri; Ismail, Nur Baini
Abstract: A graph invariant is one of the tools of topological indices used in chemical graph theory. Recently, most of chemist study in Zagreb indices and Zagreb coindices related to the connectivity of atom in molecular graph. Represented as graph, G . In this paper, we study two families of Polyphenylene dendrimers, namely D 1 [ n ] and D 2 [ n ]. We also compute their topological indices, Zagreb indices and Zagreb coindices based on the concept of the line graphs of the subdivision graphs. Furthermore, we give closed analytical results of these indices for graphs D 1 [ n ] and D 2 [ n ].